2019
DOI: 10.3390/ijms20194964
|View full text |Cite
|
Sign up to set email alerts
|

FcεRI-HDAC3-MCP1 Signaling Axis Promotes Passive Anaphylaxis Mediated by Cellular Interactions

Abstract: Anaphylaxis is an acute and life-threatening systemic reaction. Food, drug, aero-allergen and insect sting are known to induce anaphylaxis. Mast cells and basophils are known to mediate Immunoglobulin E (IgE)-dependent anaphylaxis, while macrophages, neutrophils and basophils mediate non IgE-dependent anaphylaxis. Histone deacetylases (HDACs) play various roles in biological processes by deacetylating histones and non-histones proteins. HDAC inhibitors can increase the acetylation of target proteins and affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…While activation of the pathways associated with multiple inflammatory cytokines, including IL-2, IL-6, IL-10, and TNFRI, were observed during anaphylaxis [ 6 , 9 ], the selective CCL2 chemokine cascade might be important for chemotactic activity during anaphylactic reactions. It was recently reported that the CCL2-FcεRI-histone deacetylase 3 signalling axis mediates passive anaphylaxis by increasing the expression of CCL2 in mast cells [ 28 , 29 ]. After allergen stimulation, histone deacetylase 3 binds to FcεRI, and histone deacetylase 3 increases the expression of SP1 and C-Jun, which bind to the promoter sequences of CCL2 to increase the expression of CCL2 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While activation of the pathways associated with multiple inflammatory cytokines, including IL-2, IL-6, IL-10, and TNFRI, were observed during anaphylaxis [ 6 , 9 ], the selective CCL2 chemokine cascade might be important for chemotactic activity during anaphylactic reactions. It was recently reported that the CCL2-FcεRI-histone deacetylase 3 signalling axis mediates passive anaphylaxis by increasing the expression of CCL2 in mast cells [ 28 , 29 ]. After allergen stimulation, histone deacetylase 3 binds to FcεRI, and histone deacetylase 3 increases the expression of SP1 and C-Jun, which bind to the promoter sequences of CCL2 to increase the expression of CCL2 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that the CCL2-FcεRI-histone deacetylase 3 signalling axis mediates passive anaphylaxis by increasing the expression of CCL2 in mast cells [ 28 , 29 ]. After allergen stimulation, histone deacetylase 3 binds to FcεRI, and histone deacetylase 3 increases the expression of SP1 and C-Jun, which bind to the promoter sequences of CCL2 to increase the expression of CCL2 [ 28 , 29 ]. Conversely, in the absence of allergen stimulation, histone deacetylase 3 binds to the promoter sequences of CCL2 to suppress the expression of CCL2 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously defined that, in the absence of allergen, histone deacetylase 3 binds to the promoter sequences of CCL2 to suppress CCL2 expression. Upon allergen stimulation, histone deacetylase 3 binds to FcεRI, and mediates passive anaphylaxis by increasing the expression of CCL2 in mast cells [ 33 ].…”
Section: Proinflammatory Mediators Involved In Anaphylaxismentioning
confidence: 99%
“…Permeability and anti-inflammatory effects of lornoxicon in nanoemulsions (100–200 nm) are greatly increased. Use of aspirin- or capsaicin-derived nanoemulsion reveals excellent skin penetration and permeation which is proven by laser scanning microscopy analysis [70].…”
Section: Skin Inflammationmentioning
confidence: 99%
“…Thereby, modulate activity of neurons increases SP releases from unmyelinated nerve endings of the skin, and later degranulation of cutaneous mast cells occurs [69]. A study on rats by Kim et al, [70] specified that use of siTNFα in assemblage with 2.5 mg of capsaicin nanoparticle encapsulation for 5 days yielded complete treatment of inflamed versus normal looking skin.…”
Section: Skin Inflammationmentioning
confidence: 99%